Acalculous cholecystitis with gallbladder necrosis in a patient presenting without abdominal pain. Issue 12 (17th December 2020) - Altshuler, Ellery; Case, Robert
Abstract : An 83-year-old man with a history of chronic myelogenous leukaemia in remission maintained with bosutinib presented with new-onset fevers. He denied pain and had no other focal symptoms. Ultrasound imaging revealed mild gallbladder wall thickening. Non-contrasted CT revealed right upper quadrant inflammation of indeterminate source. The diagnosis of acalculous cholecystitis was made on the third day when a CT with oral contrast demonstrated a remarkably inflamed biliary tree. The gallbladder was surgically removed and found to be necrotic. The case highlights an unusual presentation for a well-known condition. Both ultrasound and CT have limited diagnostic sensitivity for acalculous cystitis. This case adds to existing literature to support development of acalculous cholecystitis in non-critically ill patients. Clinicians should maintain awareness of this condition among patients presenting to the hospital or clinic with abdominal pain. Careful discussion with radiology and surgery is indicated to guide diagnostic testing when initial imaging results are indeterminate.